Integrating the internet of things into software engineering practices - Mala, D. Jeya, 1974- (Engineering Science Reference, 2019)
"This book presents novel ideas related to the development aspects, case studies, issues and challenges and best practices that can be adopted for IoT. It also provides details of vulnerability, complexity, robustness management, risk-driven security metrics, methodologies and tools that help the students, academia, researchers and developers to achieve adequate security, trust, dependability and privacy goals"--